Foreword - Kunz, Mieczysław; Nienartowicz, Andrzej (Ecological Questions, 2013)
Aerial and satellite remote sensing represents an important source of information and is more and more commonly used in environmental studies. The resulting products of remote data acquisition – aerial and satellite images combined with the capacity of modern tools, especially when integrated into Geographic Information Systems, facilitate multilayered analysis related to the conditions and functioning of the environment, including both its components and their mutual relations and interrelations. The aforementioned issues are discussed in papers included in the 17th volume of "Ecological Questions".